IMPROVING THE SEVENTH GRADE STUDENTS’ WRITING COMPETENCY THROUGH CLUSTERING TECHNIQUE AT SMPN 6 SINGARAJA ACADEMIC YEAR 2014/2015 - Wiguna, I.P.M.W.; Tantra, D.K.; Adnyani, L.D.S. (Universitas Pendidikan Ganesha, 2019)
This study was conducted to improve students writing skill using Clustering Technique at seventh grades students of SMPN 6 Singaraja. The Preliminary observation indicated that student class VII B4 of SMP Negeri 6 Singaraja had low writing competency. The subjects of this study were consisted of 36 students. To find out the result of students writing ability in writing competency using clustering technique, the writer used Classroom Action Research (CAR) as the method of research. This study consisted of two cycles, each cycle consisted of four steps, and they were: planning, action, observation and reflection. To collect and analyze the data, the writer used the information from observation, and the students’ achievement in preliminary and evaluation to support data collected. This study showed that using clustering technique in teaching writing can improve students writing competency.The data were collected through writing evaluation. In clustering technique, the writer can use line, boxes, arrows, and circles to show relationships among the ideas. The students’ responses showed that they were interested in writing because they felt easier to write using clustering technique. The percentage of students who had passed the passing score of writing in pre-observation were 2 students (6%), in cycle I were 14 students (39%), meanwhile in cycle II were improved into 31 students (86%). It could be concluded that the implementation of Clustering technique could improve the students’ writing ability of students class VII B4 at SMP Negeri 6 Singaraja. And The writer suggested to the other English teacher to use Clustering Technique in teaching writing, because this technique helps the students organize their ideas before they start to write. Key words: Writing competency, Clustering Technique